Dating of the GV7 East Antarctic ice core by high-resolution chemical records and focus on the accumulation rate variability in the last millennium - Nardin R.; Severi M.; Amore A.; Becagli S.; Burgay F.; Caiazzo L.; Ciardini V.; Dreossi G.; Frezzotti M.; Hong S. -B.; Khan I.; Narcisi B. M.; et al. (Climate of the Past, 2021)
Ice core dating is the first step for a correct interpretation of climatic and environmental changes. In this work, we release the dating of the uppermost 197g m of the 250g m deep GV7(B) ice core (drill site, 70g 41g S, 158g 52g E; 1950g mg a.s.l. in Oates Land, East Antarctica) with a sub-Annual resolution. Chemical records of NO3-, MSA (methanesulfonic acid), non-sea-salt SO42-(nssSO42-), sea-salt ions and water stable isotopes (I18O) were studied as candidates for dating due to their seasonal pattern. Different procedures were tested but the nssSO42-record proved to be the most reliable on the short-and long-Term scales, so it was chosen for annual layer counting along the whole ice core. The dating was constrained by using volcanic signatures from historically known events as tie points, thus providing an accurate age-depth relationship for the period 1179-2009g CE. The achievement of the complete age scale allowed us to calculate the annual mean accumulation rate throughout the analyzed 197g m of the core, yielding an annually resolved history of the snow accumulation on site in the last millennium. A small yet consistent rise in accumulation rate (Tr Combining double low line 1.6, p<0.001) was found for the last 830 years starting around mid-18th century.